Oceans of the world - "Wells, Susan" (Horus Editions London, 2003)
"Oceans of the World" by Susan Wells, published by Award Publications Ltd in 2003. This 64-page paperback is part of the "Explorer" series and offers insights into the world's oceans, likely covering topics such as marine life, oceanography, and environmental aspects.